GABA(A) receptors are expressed and facilitate relaxation in airway smooth muscle - Mizuta, Kentaro (2008)
γ-Aminobutyric acid (GABA) is the major inhibitory neurotransmitter in the mammalian central nervous system and exerts its actions via both ionotropic (GABA(A)) channels and metabotropic (GABA(B)) receptors. GABA(A) channels are ubiquitously expressed in neuronal tissues, and in mature neurons modulate an inward chloride current resulting in neuronal inhibition due to membrane hyperpolarization. In airway smooth muscle (ASM) cells, membrane hyperpolarization favors smooth muscle relaxation. Although GABA(A) channels and GABA(B) receptors have been functionally identified on peripheral nerves in the lung, GABA(A) channels have never been identified on ASM itself. We detected the mRNA encoding of the GABA(A) α(4)-, α(5)-, β(3)-, δ-, γ(1–3)-, π-, and θ-subunits in total RNA isolated from native human and guinea pig ASM and from cultured human ASM cells. Selected immunoblots identified the GABA(A) α(4)-, α(5)-, β(3)-, and γ(2)-subunit proteins in native human and guinea pig ASM and cultured human ASM cells. The GABA(A) β(3)-subunit protein was immunohistochemically localized to ASM in guinea pig tracheal rings. While muscimol, a specific GABA(A) channel agonist, did not affect the magnitude or the time to peak contractile effect of substance P, it directly concentration dependently relaxed a tachykinin-induced contraction in guinea pig tracheal rings, which was inhibited by the GABA(A)-selective antagonist gabazine. Muscimol also relaxed a contraction induced by an alternative contractile agonist histamine. These results demonstrate that functional GABA(A) channels are expressed on ASM and suggest a novel therapeutic target for the relaxation of ASM in diseases such as asthma and chronic obstructive lung disease.